Relative abundance of harbour porpoises (Phocoena phocoena) from acoustic and visual surveys of the Baltic Sea and adjacent waters during 2001 and 2002 - Gillespie, D.; Berggren , P.; Brown , S.; Kuklik , I.; Lacey , C.; Lewis , T.; Matthews , J.; McLanaghan , R.; Moscrop , A.; Tregenza , N. (J. Cetacean Res. Manage., 2023)
Boat-based acoustic and visual surveys for harbour porpoises (Phocoena phocoena) were conducted during the summers of 2001 and 2002 in order to investigate their distribution and relative abundance in the Baltic Sea, and to compare the results with the adjacent Kiel and Mecklenburg Bights and the Little Belt. Harbour porpoises are subject to year-round bycatch in gillnets and other fishing gear in these waters. This is of particular concern in the Baltic Sea where a survey carried out in 1995 indicated that the population is low and current levels of anthropogenic mortality are believed to be unsustainable. Polish coastal waters were not included in the 1995 survey and it has been hypothesised that these unsurveyed waters may contain a significant uncounted part of the Baltic Sea population. Results show that the porpoise detection rate was two orders of magnitude lower in the Baltic Sea than in other waters surveyed. No evidence was found that Polish waters contain a significant, previously uncounted part of the Baltic Sea population. The results confirm the endangered status of the Baltic Sea population, and stress the urgency of preventing future anthropogenic mortalities that threaten the survival of the population.